Integrating business and society’s five frameworks: A critical appraisal of Schwartz and Carroll's proposal in the context of South African corporate governance and business ethics - Beale, Thomas Jason (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.